The Joint Determination of Marginal Rate of Return and Interest Adjusted Cost for Whole Life Insurance - Schleef, Harold J. (Management Science, 1983)
Linear programming is applied to measurement of whole life insurance to obtain a functional relationship between interest adjusted cost of insurance protection and rate of return on policy equity. For comparative purposes, policy differences related to premium rates, dividends and cash-values are controlled by maintaining identical insurance requirements and constant levels of wealth for the insured. Marginal discount factors, obtained from the dual variables for the wealth constraints, demonstrate the importance of policy holder wealth. The interest adjusted cost measure currently used by the insurance industry is shown to be a special case when the linear programming approach is used. The method used in this paper is sufficiently flexible to incorporate different patterns of time preference for insurance. Finally, it is demonstrated that the trade-off between interest adjusted cost of insurance and rate of return on policy equity is sensitive to the external rate of return.